The Correlation Between Students’ Vocabulary Mastery And Speaking Ability of Eight-Grade Students at MTs Negeri 1 Tanjung Pura - Krishna Ardian; Rachma Muta’ali S H; Balielah Alandalousiyyah; Edi Suprayetno (English Lecturers and Teachers Association (ELTA), 2023)
In an era of increasingly advanced globalization, the ability to speak English is essential to keep up with the changing times. This study was to analyze the correlation between students' vocabulary mastery and speaking skills of grade eight students at MTs Negeri 1 Tanjung Pura. The sample of this study was 15 students of class VIII B which were taken by using a purposive sampling technique. This study was a correlational method in a quantitative design by using correlation statistical tests to describe and measure between two or more variables. The Correlation Product Moment formula using SPSS was used to determine if there is a correlation and degree of correlation between English vocabulary mastery and speaking skills. From the data analysis it was found that there was a correlation between vocabulary mastery and speaking skill of grade eight students of MTs Negeri 1 Tanjung Pura with the level correlation value was 0,559 or 55,90 % or on the level of “Fair” Correlation. Keywords: Vocabulary Mastery; Speaking Skill